Mobile-oriented Learning: Developing and Using Infoword Application «Informatics Dictionary» - O. Petrichenko, Larisa; V. Bakhmat, Nataliia; V. Tsypko, Victoriia; V. Liubarets, Vladyslava; O. Prokopenko, Alona (International Journal of Psychosocial Rehabilitation, 2020)
In the article, the authors presented the working out and use of the application «Informatics Dictionary» to improve the quality of future teachers’ training. Based on the analysis of scientific, pedagogical, and special literature, researchers have come to the conclusion that during the global technological progress, the use of mobile applications is the requirement for a modern educational process, and the educational process becomes simply impossible without the use of innovative information and communication technologies. Thus, mobile-oriented learning is replaced by a traditional education system. In the process of scientific research, the researchers analyzed three of the most popular graphic constructors for creating mobile applications: Alstrapp, Appsgeyser, and Appsmakerstore. In a detailed analysis of these constructors, their advantages and disadvantages were determined. The authors of the article assigned the following disadvantages: problems with downloading APK files; free use of these constructors only for administrator-defined terms; hidden fees for using certain app tabs; purchase of a license (from 90 and above); the lack of interconnection with the customer support service; and the lack or imperfection of an interface for creating educational applications, etc. Scientists have proposed an algorithm for developing their own mobile application by writing it in the Java programming language. The advantages for the author of the application are revealed: constructive thinking, creativity, and professional skills develop, and programming skills are improved during the working-out of this application. The researchers are presented in detail the experience of using the author’s application, “Informatics Dictionary,” to improve the quality of future teachers’ training. There was research from 2017 to 2019, during which the results of control tests were analyzed and a poll of students about the use of mobile applications in the learning process was conducted. Taking into account the results of the work, the authors conclude that the use of mobile-oriented learning is a requirement of the present day because today every student uses mobile devices in daily life and during the educational process. Prospects for further research are to conduct seminars for students about the working out of mobile applications.